ISLAM, PANCASILA AND VALUE SYSTEMS OF INDONESIAN NATIONAL EDUCATION - DR. Martha Catherine Beck; Irawan Irawan (Jurnal Pendidikan Islam, 2014)
This paper intends to show that the Pancasila (five principles of state) and the Pillarsof Islam (the five religious value system) has synergy to build Indonesia's nationaleducation values system. To explore the relation between religion and politics inPancasila, Martha Beck used Alfred North Whitehead's process philosophy, CarlGustav Jung's archetypes psychology and Ervin Laszlo‟s systems theory. To approvethat Pancasila and Pillars of Islam has synergy to Indonesia‟s national education,Irawan used the concept of scientia sacra by Seyyed Hossein Nasr. The results showedthat the Indonesian national education system consistently present in a triangularrelationship between religion (spiritual humanism), politics (democracy) and cultural(multicultural and tolerance). The relationship manifested in Indonesian NationalEducation System, which is always grounded philosophically and aims at threethings; 1) form human who believe, cautious and has noble character; 2) master ofscience and technology; and 3) actively participate in creating order and peace in theworld, even a blessing for the entire universe. Indonesia's national education systemcould be a new alternative in building a more holistic education systems around theworld because considered crucial interconnection between science, religion, interestsof state and demands of the global. This is known as a moderate Islamic education.